2018
DOI: 10.3892/mmr.2018.8688
|View full text |Cite
|
Sign up to set email alerts
|

Role of SGLT1 in high glucose level-induced MMP-2 expression in human cardiac fibroblasts

Abstract: Cardiac fibrosis is a major pathological manifestation of diabetic cardiomyopathy (DCM), which leads to cardiac remodeling, dilated cardiomyopathy and congestive heart failure. Human cardiac fibroblasts (HCF) constitute the predominant cell type in the heart and matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) are also involved in cardiac fibrosis. However, it is unclear whether high glucose levels affect the expression of MMPs and TIMPs in HCF. Sodium‑glucose cotransporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…The latter is a shared pathology in HF patients with and without diabetes [8]. In response to high glucose concentrations, SGLT1 contributed to cellular glucotoxicity in cultured rat cardiomyocytes via increased activation of NAPDH-oxidase [45], whereas it facilitated profibrotic signaling in human cardiac fibroblasts [46]. Nonetheless, in the present study, immunohistochemical staining of SGLT1 suggested that cardiomyocytes-but not fibrotic tissue-are the primary sources of SGLT1 expression in the myocardium, in line with Kashiwagi et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a shared pathology in HF patients with and without diabetes [8]. In response to high glucose concentrations, SGLT1 contributed to cellular glucotoxicity in cultured rat cardiomyocytes via increased activation of NAPDH-oxidase [45], whereas it facilitated profibrotic signaling in human cardiac fibroblasts [46]. Nonetheless, in the present study, immunohistochemical staining of SGLT1 suggested that cardiomyocytes-but not fibrotic tissue-are the primary sources of SGLT1 expression in the myocardium, in line with Kashiwagi et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…There may also be some compensatory mechanisms activated in those mouse hearts by the permanent knock-down of cardiac SGLT1 from birth. Considering that the SGLT1 expression is chronically increased under diabetic conditions [19,21], resulting in detrimental effects [21,25,40], it is important to attain the effects of SGLT1 on the cardiac function as well as energy metabolism during acute phase of IRI, particularly in insulin-resistant diabetic models. We found in the present study that, under insulin-resistant conditions, SGLT1 isoform may play a compensatory protective role during the loss of GLUT4-mediated glucose uptake, rather than provides detrimental impacts on the diabetic myocardium [21,25], at least during the acute phase of IRI.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to assess the expression of those glucose transporters in isolated cardiomyocytes, considering that not only myocardial SGLT1 and other glucose transporters but also those residing in cardiac fibroblasts [40] and endothelial cells [67] may play a substantial role under diverse pathological conditions, such as ischemic heart diseases as well as diabetes (insulin resistant conditions), and the regulation of the expression of those glucose transporters might differ among cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this finding, transgenic overexpression of cardiac SGLT1 was associated with myocardial hypertrophy and left ventricular dysfunction that was reversible by SGLT1 suppression. In another study, human cardiac fibroblasts exposed to high glucose levels increased expression of proteins involved in cardiac fibrosis (i.e., matrix metalloproteinase-2) that was reversed by phlorizin (a dual SGLT1 and SGLT2 inhibitor) but not by dapagliflozin (an SGLT2 inhibitor) (31). In addition to our data, these studies provide support for the role of SGLT1 as a cardiac sodium/glucose transporter that may be involved in cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%